2020
DOI: 10.1186/s12935-020-01450-1
|View full text |Cite
|
Sign up to set email alerts
|

The biological function of m6A demethylase ALKBH5 and its role in human disease

Abstract: Human AlkB homolog H5 (ALKBH5) is a primary m6A demethylase, which is dysregulated and acts as a biological and pharmacological role in human cancers or non-cancers. ALKBH5 plays a dual role in various cancers through regulating kinds of biological processes, such as proliferation, migration, invasion, metastasis and tumor growth. In addition, it takes a great part in human non-cancer, including reproductive system diseases. The underlying regulatory mechanisms of ALKBH5 that relys on m6A-dependent modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 49 publications
(93 reference statements)
1
115
0
Order By: Relevance
“…ALKBH5 contains a DSBH domain, which can bind to the ATP domain of DDX3 gene, thus affecting cell cycle, apoptosis, RNA degradation and other cellular processes [31]. In the present study, ALKBH5 expressions was varied in different malignant tumors.…”
Section: Discussionmentioning
confidence: 58%
“…ALKBH5 contains a DSBH domain, which can bind to the ATP domain of DDX3 gene, thus affecting cell cycle, apoptosis, RNA degradation and other cellular processes [31]. In the present study, ALKBH5 expressions was varied in different malignant tumors.…”
Section: Discussionmentioning
confidence: 58%
“…YTHDF2, as a member of m6A "readers", can selectively recognize and bind to m6A-containing RNA to initiate its degradation in a deadenylation-dependent manner by interacting directly with the SH domain of CNOT1, the scaffolding subunit of the CCR4-NOT deadenylase complex [33]. Accumulating evidences have demonstrated that YTHDF2 can act as an oncogene cooperating with dysregulated "writers" or "erasers" via degrading m6A-containg tumor-inhibiting factors [49]. For example, the overexpression of METTL3 and YTHDF2 in bladder cancer can promote cell proliferation and migration via the decay of tumor suppressors Kruppel-like factor 4 (KLF4) and SET domain containing 7 (SETD7) [50].…”
Section: Discussionmentioning
confidence: 99%
“…The installation of m6A is catalyzed by writers/methyltransferase complex (MTX), including methyltransferase-like protein 3 (METTL3), METTL14, METTL16, WT1-associated protein (WTAP), RNA-binding motif protein 15 (RBM15), RBM15B, KIAA1429 (or named VIRMA) and zinc nger CCCH-type containing 13 (ZC3H13) [9,10]. Eraser is a class of demethylases, including fat mass and obesity-associated protein (FTO), α-ketoglutarate-dependent dioxygenase homolog 5 (ALKBH5) and ALKBH3 [11][12][13]. Read proteins can recognize speci c m6A sites and regulate the biofunction of target RNA.…”
Section: Introductionmentioning
confidence: 99%
“…NANOG contributes to tumor cell growth and TMZ resistance in glioma [19,20]. N6-methyladenosine (m6A) is a common mRNA modi cation, and it is involved in the regulation of noncoding RNAs on tumorigenesis [21].AlkB homolog H5 (ALKBH5) is a representative m6A demethylase which can lead to the demethylation of mRNA in human disease [22]. ALKBH5 maintains tumorigenicity of glioma stem-like cells [23].…”
Section: Introductionmentioning
confidence: 99%